Item Analysis of Critical Thinking Skills Instrument to Measure Effectiveness of Scientific Group Inquiry Learning (SGIL) Model - Wijayanti, M. D.; Rahardjo, S. B.; Saputro, S.; Mulyani, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
The purpose of this study is to analyze the problem set items to get information and feedback on critical thinking skills tests. This research develops a SGIL model that can improve students’ critical thinking learning. This study uses a research and development design to develop the SGIL model. The SGIL model is proven to be able to improve the critical understanding of PGSD students. The syntax of SGIL consists of 6 steps, namely: (1) discussion of problems and topic selection; (2) research planning; (3) implementation; (4) data integration; (5) analysis and synthesis; and (6) conclusions and communication. The participants were 114 Elementary Teacher Education Program (PGSD) students who were selected by using a random sampling technique. This research was conducted in 3 sample universities. The data of SGIL model effectiveness was measured by using instrument of critical thinking skills. This instrument has been analyzed for its validity, reliability, level of difficulty, and discrimination item. Tests to obtain data were carried out for 90 minutes. The instrument was calculated by using analysis of Quest and Lisrel.